Penerapan Metode Pembelajaran Jigsaw Dikombinasikan dengan Media Power Point untuk Meningkatkan Aktivitas dan Prestasi Belajar Pendidikan Agama Hindu dan Budi Pekerti - Damayanti, Putu Mega; Mastiningsih, Ni Nyoman; Suarnaya, I Putu (STKIP AGAMA HINDU SINGARAJA, 2023)
The problem studied in this study is the low activity and learning achievement of Hinduism and Moral Education in class XI Multimedia SMK TI Bali Global Singaraja Academic Year 2022/2023. The purpose of this study is to examine the application of the Jigsaw Learning model combined with Powerpoint media to increase learning activities and achievement in class XI Multimedia at SMK TI Bali Global Singaraja for the 2022/2023 academic year. In order to achieve the above objectives, several theories are used, including: The Jigsaw learning method, Powerpoint media and relevant research results. The research was designed using the Classroom Action Research method with 15 research subjects consisting of 11 male students and 4 female students at SMK TI Bali Global Singaraja. The research procedure uses a cycle system consisting of 2 cycles, where each cycle consists of 4 (four) stages, namely: planning, action implementation, observation evaluation analysis, and reflection. The data collection method used tests for academic knowledge data, then observations for student activity data on learning Hindu Religious Education and Character. The results of the research can be explained as follows: in the implementation of the first cycle, the average student attitude towards learning was 55.8% and the average academic knowledge of the class (M) was 76.7, the classical absorption (DS) was 76.7% and the mastery learning (KB) 40% Low category. Then the implementation of cycle II The average student attitude towards learning was 85.8% and the average academic knowledge of class was 88, classical absorption (DS) 88%, and classical learning mastery (KB) 100% High category. The results of the research are recommended to teachers, especially Hindu Religion teachers, to apply the Jigsaw Learning method combined with Powerpoint media correctly and correctly in an effort to increase student activity and achievement.